Cacao agroforestry systems beyond the stigmas: Biotic and abiotic stress incidence impact - Jaimes-Suárez, Yeirme Y.; Carvajal-Rivera, Albert S.; Galvis-Neira, Donald A.; Carvalho, Fabricio E. L.; Rojas-Molina, Jairo (Frontiers in Plant Science, 2022)
Low technological knowledge in production chains, global climate change, and misinformation are concrete threats to food security. In addition, these combined threats also trigger ecological instability in megadiverse areas of the world, especially in some cacao-producing countries in South America, where this crop plays an important socio-economic role, even being used to replace illicit crops. Accordingly, the use of agroforestry systems approaches has emerged as a good alternative to maintain productivity, add high-value commodities to producers, and provide important ecosystem services for sustainable agriculture. However, limitations associated with the competition for resources between the species composing the system, and the higher incidence of some diseases, have led many producers to abandon this strategy, opting for monoculture. In this review, we seek to gather the main information available in the literature, aiming to answer the question: what is the real scientific evidence that supports the benefits and harms of adopting agroforestry systems in cacao production? We seek to make critical scrutiny of the possible negative effects of certain associations of the agroforestry system with biotic and abiotic stress in cacao. Here, we review the possible competition for light and nutrients, and discuss the main characteristics to be sought in cacao genotypes to optimize these inter-specific relationships. In addition, we review the research advances that show the behavior of the main cacao diseases (Witch's broom disease, Frosty Pod Rot, Black pod rot) in models of agroforestry systems contrasted with monoculture, as well as the optimization of agronomic practices to reduce some of these stresses. This compendium, therefore, sheds light on a major gap in establishing truly sustainable agriculture, which has been treated much more from the perspective of negative stigma than from the real technological advantages that can be combined to the benefit of a balanced ecosystem with generating income for farmers.